UPAYA MENUMBUHKAN PEMAHAMAN INTEGRATIF PESERTA DIDIK DALAM PEMB MELALUI APRESIASI BUDAYA - Wardayati, Esti Dwi (HISTORIKA, 2016)
Social Science Learning that takes place in schools is still impressed. Contextual learning can be used in Social Science learning by utilizing the environmental potential optimally to make it more meaningful. Potential local lingkungna particularly the culture and local traditions can be utilized in the process of learning so that students will be more appreciate culture. The learning process with the implementation of the social science model learning CTL audiovisual media with a local tradition in practice can enable and streamline the learning of students. It is characterized by the observations of the student activities during the following process of teaching and learning. Observation on the activity of students can be monitored with the observation sheets covering aspects of the liveliness of the asking, the defence's opinion, initiative and appreciate your time. From the radar of researchers, noted increasing student activity. In addition teachers skills in managing class is also increasing.